Diksi dan Gaya Bahasa Al-Hadīts Tentang Mukmīn dan Munāfik pada Pembacaan Qur`ān (Kajian Stilistika) - Dedi Ramadhan (Universitas Muhammadiyah Gorontalo, 2022)
This study aims to examine the stylistic aspects of hadith about believers and hypocrites in reading the qur`ān. The data of this study were collected from hadith books through seven famous narrators which were accessed with the maktabah al-syāmilah application. This research is a descriptive qualitative analytical method with five levels of stylistic analysis in general, namely: phonology, morphology, syntax, semantics, and imagery. To analyze data through stylistics with content analysis techniques. This analysis technique is intended as a data analysis technique consisting of data reduction stages, data presentation stages, and data verification stages. The result of this research is that the hadith contains a distinctive style of language and many meanings in it.